The effect of a finger training application using a tablet PC in chronic hemiparetic stroke patients. (2nd April 2016) - Jang, Sung Ho; Jang, Woo Hyuk
Abstract: Twenty-one consecutive patients were randomly assigned to either the intervention group (10 patients) or the control group (11 patients). The application consisted of three sections (registration, evaluation, and training) and the training section consisted of five programs (stretching, flexion, extension, opposition, and thumb abduction). Application training consisted of 1 session (31 min)/day, 6 days/week for 4 weeks. We found that our application training was effective in terms of the motor function of the affected hand: Manual Muscle Test of the wrist and finger extensors, the Manual Function Test (subtest of manipulative activity), and the Purdue Pegboard Test.